Does sophistication affect long-term return expectations? Evidence from financial advisers' exam scores - Markku Kaustia; Antti Lehtoranta; Vesa Puttonen (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
We use unique data fromfinancial advisers' professional exam scores and combine it with other variables to create an index of financial sophistication. Using this index to explain long-term stock return expectations, we find that more sophisticated financial advisers tend to have lower return expectations. A one standard deviation increase in the sophistication index reduces expected returns by 1.1 percentage points. The effect is stronger for emerging market stocks (2.3 percentage points). The sophistication effect contributes 60% to the model fit, while employer fixed effects combined contribute less than 30%. These results help understand the formation of potentially excessively optimistic expectations.
urn:nbn:de:hebis:30:3-293716
Keywords: D84; G11; G24; 330; stock return expectations; sophistication; financial literacy; adviser